Penerapan Model Pembelajaran Tipe Cooperative Script Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Arab Kelas XII MA - Amir Amir (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study is the low student learning outcomes in Arabic subjects for Class XI students at MA AT-Taufiq Lisu, Barru Regency. The approach used in this research is descriptive qualitative with this type of research is Classroom Action Research (CAR) which has a cycle which includes planning, implementation, observation, and reflection. The focus of the research is the application of the Cooperative Script cooperative learning model to improve student learning outcomes in Arabic class XII MA AT-Taufiq Lisu, Barru Regency. The research setting was carried out in Class XII with the research subjects consisting of teachers and 15 students of class XII. The results showed that there was an increase in activity in teacher learning and student learning activities as well as Arabic learning outcomes, the increase could be seen from each cycle, namely in cycles 1 and 2. student learning in Arabic subjects Class XI MA Cooperative Script Barru